Size, season and offspring sex affect milk composition and juvenile survival in wild kangaroos. (23rd March 2017) - Quesnel, L.; MacKay, A.; Forsyth, D. M.; Nicholas, K. R.; Festa‐Bianchet, M.
Abstract: The main component of mammalian maternal care is milk production. The composition of milk has been hypothesized to determine offspring survival, and to vary with offspring sex. Few studies, however, have examined variation in milk composition of wild mammals in seasonal environments, where environmental conditions can impact the ability of mothers to provide care. We investigated individual differences in milk composition and offspring survival in wild eastern grey kangaroos ( Macropus giganteus ). We analyzed total protein and lipid concentrations in 103 milk samples from 91 females over 2 years. In a year of low forage production, few females that lactated were in poorer condition and produced milk of lower energy content compared to females lactating in a year of high forage production. Females nursing in late winter produced milk with more lipids compared to females at the same stage of lactation in late spring, whose milk had a higher proportion of protein. The milk of larger females contained more protein than lipid, and females in better condition allocated higher proportions of protein to sons than to daughters. Increased protein concentration in milk was correlated with offspring longevity, and this effect was stronger for sons than daughters. A seasonally modulated lactation strategy enables the adjustment of milk composition to available resources. Condition‐specific protein allocation in favor of sons for mothers of higher caring ability suggests adaptive sex‐biased maternal care in this highly sexually dimorphic mammal. Abstract : The main component of mammalian maternal care is milk production. We investigated individual differences in milk composition and offspring survival in wild eastern grey kangaroos ( Macropus giganteus ). We analyzed total protein and lipid concentrations in 103 milk samples from 91 females over two years. Females nursing in late winter produced milk with more lipids compared to females lactating in late spring, larger females produced higher‐protein milk than smaller females, and protein content in the milk was associated with better male‐offspring longevity. A seasonally modulated lactation strategy enabled the adjustment of milk composition to available resources, and condition‐specific protein allocation in favor of sons for mothers of higher caring ability suggests adaptive sex‐biased maternal care in this highly sexually dimorphic mammal.